PENGARUH PERMAINAN TRADISIONAL TERHADAP KETERAMPILAN SOSIAL ANAK USIA 5-6 TAHUN DI TK AL-MA’AARIJ BEKASI TIMUR - Hera Oktaviani; Pujianti, Yuli; Sofia Trisna Sazain; Sabila Nur Masturah; Nabil (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2023)
Early Childhood Education is a crucial first step for children in their social development. Social skills play a vital role in early childhood learning as children learn to navigate new environments, adapt to new people, and prepare themselves for future schooling. Early Childhood Education provides a foundation for children to develop the necessary skills and readiness to progress to the next level of education. This study focuses on the social skills of children aged 5-6 years at Al-Ma'aarij Kindergarten in East Bekasi. It examines the impact of traditional games on the social skills of children in the 5-6 year old group (Group B). The study only involves one group, which is the 5-6 year old group. The research method used in this study is quantitative experimentation, with the purposive sampling technique. Purposive sampling is where the researcher chooses a sample group based on predetermined criteria. In this study, the sample group consisted of children with insufficient social skills. The primary sources of data were the researchers' field observations and the results of instruments used to observe children. The secondary data were obtained from reference books and journals related to social skills and traditional games. To calculate the research data, the researchers conducted a normality test using the Liliefors test and a homogeneity test using the F test.